IMPLEMENTATION OF ILLEGAL PARKING HANDLING POLICIES IN JAYAPURA CITY - Corry Yapen; Yoshepine Ohoiwutun; Nur Aeda (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze the implementation of illegal parking management policies in Jayapura City and its impact on Regional Original Revenue (PAD). The main problem lies in the increasing number of vehicles that are not balanced with the availability of parking facilities, thus triggering illegal parking practices and regional levy leakage. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The analysis was conducted using the perspective of George C. Edward III's policy implementation theory and Michael Lipsky's street-level bureaucracy concept. The results of the study show that policy implementation has not been optimal. From Edward III's perspective, weaknesses can be seen in ineffective communication aspects, limited resources, weak implementation dispositions, and bureaucratic structures that are not synergistic. Meanwhile, Lipsky's perspective shows that the high use of discretion by field officials is a mechanism for adapting to limitations, but it also causes inconsistencies, legal uncertainties, and potential injustices. In addition, the practice of prioritization, simplification of tasks, and a compromising approach in interactions with the community widens the gap between formal policies and practices in the field. Therefore, it is necessary to strengthen institutional capacity, improve coordination between agencies, and prepare clear operational guidelines to balance flexibility and standardization. Thus, policy implementation is expected to be more effective, accountable, and able to increase contributions to PAD.